Development of Bean-Based Emulgels for 3d Printing Applications: Feasibility for Dysphagia Diets - Rivera-Tobar, D (Elsevier Ltd, 2023)
Emulgels could be used as edible inks for individuals with special needs. The purpose of this work was to formulate a 3D printable low-oil emulgel by evaluating the effect of incorporating gelatin in a bean-based nanoemulsion stabilized by high-pressure homogenization (HPH) suitable for a dysphagia diet. The effect of physicochemical properties and printing parameters of the emulsion network were evaluated for printability, dimensional stability, and textural properties. HPH produced stable nanoemulsions using pressures >200 MPa and 5% bean protein. Adding gelatin decreased NH and COO vibrations, increased hydrogen bonding, and created self-supporting emulgels when the gelatin concentration was >1.5%. Printing performance, dimensional stability, and textural properties depended on the gelatin concentration and printing parameters, whose improvement enabled precise, time-stable, and swallow-safe shapes with 2.5% gelatin. In conclusion, stable emulgels can be used in 3D printing, facilitating the design of colloidal food systems with customized textures and nutritional properties for individuals with dysphagia. © 2023